The impact of pharmaceutical care intervention on the depressive symptoms of patients diagnosed with hypothyroidism - Malik Kamil, Rafal; Vian Ahmed Wasta Esmail; Dler Shamsulddin Hamid * (Iraqi Journal of Pharmaceutical Sciences, 2023)
Pharmaceutical care interventions are a set of recommendations/interventions given by the pharmacist to improve therapeutic compliance, reduce complications, solve a drug therapy problem and improve patients’ quality of life with chronic diseases by achieving patient satisfaction. The role of pharmaceutical care intervention in improving the condition of patients with hypothyroidism is still uncovered in Sulaimani city in Iraq, therefore, the current study aimed to evaluate the role of pharmaceutical care interventions in improving the outcome of psychological abnormalities in patients diagnosed with hypothyroidism. Fifty-eight patients were enrolled in the study and were randomly allocated into two groups: pharmaceutical care and the control group, both groups were interviewed by the pharmacist using a specific questionnaire. It is the fourth version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) for assessing their psychological state at the beginning and the at the end of the study and data are recorded by the pharmacist. Blood samples were collected and utilized for analyzing the levels of thyroid function tests, lipid profile tests and blood glucose parameters at baseline and six weeks after. The pharmaceutical care group received all the education about their medications and how to minimize drug-related problems; improve the outcome and quality of life. Additionally, the pharmaceutical intervention included correcting some biochemical parameters. The study findings suggest that pharmaceutical care intervention and the pharmacist’s role over six-weeks period could improve the patient’s psychological condition. In addition, it can improve some biochemical parameters and quality of life significantly.